1998
DOI: 10.1021/ac980656z
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Prototyping of Microfluidic Systems in Poly(dimethylsiloxane)

Abstract: This paper describes a procedure that makes it possible to design and fabricate (including sealing) microfluidic systems in an elastomeric material [Formula: see text] poly(dimethylsiloxane) (PDMS) [Formula: see text] in less than 24 h. A network of microfluidic channels (with width >20 μm) is designed in a CAD program. This design is converted into a transparency by a high-resolution printer; this transparency is used as a mask in photolithography to create a master in positive relief photoresist. PDMS cast a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
4,081
0
21

Year Published

1999
1999
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 4,852 publications
(4,120 citation statements)
references
References 81 publications
(229 reference statements)
18
4,081
0
21
Order By: Relevance
“…Oxygen plasma treatments are usually used to modify the wettability of PDMS for applications like microfluidic devices. 33 The surface of PDMS can be oxidized under the plasma treatment, leading to the formation of polar chemical species such as silanol groups (Si−OH). 34 These polar groups make the exposed surface hydrophilic.…”
Section: Resultsmentioning
confidence: 99%
“…Oxygen plasma treatments are usually used to modify the wettability of PDMS for applications like microfluidic devices. 33 The surface of PDMS can be oxidized under the plasma treatment, leading to the formation of polar chemical species such as silanol groups (Si−OH). 34 These polar groups make the exposed surface hydrophilic.…”
Section: Resultsmentioning
confidence: 99%
“…Duffy et al 2 first introduced 'rapid prototyping of masters' whereby they used printed transparencies to replace the expensive chrome masks traditionally utilized in photolithography. The authors demonstrated the advantages of using rapid prototyping for masks over conventional photolithography and micromachining.…”
Section: Introductionmentioning
confidence: 99%
“…The small sample and reagent requirements, rapid analysis times, high throughput processing capabilities, and low operating costs are among the driving forces for the development of these systems [5][6][7][8]. Different microfluidic devices have been applied to specific aspects of protein processing, in particular, protein purification and separation, protein digestion, and protein identification by mass spectrometry [9].…”
mentioning
confidence: 99%